Optimized micro grids integrated with renewable energy sources for rural households - AKHIL P. SEBASTIAN LEKSHMI A.V NIMISH K.C; Dr. Geetha Susan Philip (Guide) (Tavanur 2012 DEPARTMENT OF FARM POWER, MACHINERY AND ENERGY)
Optimized micro grids integrated with renewable energy sources for rural households
Optimized micro grids integrated with renewable energy sources for rural households